(3EOGQI GdJMhd h GdbjGOI GdaYGdI (B/s - (3WGgQ, YdGA aQLs ((3YeGf(B: s (3OGQ GdQGjI ddfTQ hGdJhRjY(B, s, 2010)
(3CSGSjGJ aj WHjYI h eaghe GdGOGQI, GdGOGQI h GdQCj GdYGe h GdGYdGe, CHYGO GdYedjI GdGOGQjI, GdJhLjg h GdQbGHI GOGQI GdJMhd h GdJZjjQ, EOGQI GdJMhd h eaghe GdPGJ ddaQO h GdefTCI, EOGQI GdJMhd h GdGHOGY GdGOGQj h GdJfXjej h CNjQG EOGQI GdJMhd h GdJOQjHs
(3HHdjhZQGajG(B: (3U(B.153s
Keywords: (3EOGQI GdCaQGOs; (3GdEOGQIs; (3GdbjGOIs